The effect of three different warm-up intensities on kayak ergometer performance - Bishop, D.; Bonetti, D.; Dawson, B. (Medicine & Science in Sports & Exercise, 2001)
Purpose:The purpose of this study was to investigate the influence of warm-up (WU) intensity on supramaximal kayak ergometer performance. Methods: In the initial testing session, eight institute of sport kayak squad members performed a graded exercise test for determination of VO2max and lactate (La) parameters. In a random, counterbalanced order, subjects subsequently performed WU for 15-min at either their aerobic threshold (W1), their anaerobic threshold (W3), or mid-way between their aerobic threshold and anaerobic threshold (W2). A 5-min passive rest period and then a 2-min, all-out kayak ergometer test followed the WU. Results: For the three different WU conditions, no significant differences were observed for average power, peak VO2, total VO2, total VCO2, or accumulated oxygen deficit (AOD) during the 2-min test. However, when compared with W3, differences in average power approached significance after both W1 (P = 0.09) and W2 (P = 0.10). Furthermore, when compared with W3, average power during the first half of the 2-min test was significantly greater after W2 (P < 0.05) and approached significance after W1 (P = 0.06). After each WU period, there was a significant difference in blood pH (W1>W2>W3; P < 0.05) and blood [La] (W1<W2<W3; P < 0.05). Despite the significantly different metabolic acidemia after each WU condition, there were no significant differences in the VO2 responses to the 2-min test. However, the greater metabolic acidemia after W3 was associated with impaired 2-min kayak ergometer performance. Conclusions: It was concluded, that although a degree of metabolic acidemia may be necessary to speed O2 kinetics, if the WU is too intense, the associated metabolic acidemia may impair supramaximal performance by reducing the anaerobic energy contribution and/or interfering with muscle contractile processes.